Analysis of High School Students, Needs for E-Comics Assisted by Figma and Flipbook on Reading Material og Malay Figure Biography Texts - Ulfa, Risky Yanti; Hermandra, Hermandra; Sinaga, Mangatur (Journal of Educational Sciences, 2025)
This study is a stage in the development of e-comics assisted by figma and flipbooks on the material of reading biographical texts for high school students. This study aims to describe the analysis of student needs for learning to read biographical texts. The survey method in the research method used in this study. The data collection instrument in this study is a needs analysis questionnaire. This study uses a Likert scale to measure students' views and perceptions of the e-comics developed. This study uses a questionnaire sheet made in the form of a closed statement with a scoring range of 1 to 5. The questionnaires compiled were addressed to students in two high schools in Pekanbaru City. This sampling technique is based on the sampling quota determined by the researcher. The data analysis technique is carried out by changing the category value into an assessment score and analyzing the score. The results showed that 87.70% of students had difficulty in learning to read biographical texts and 88.74% of students wanted learning to read biographical texts to be presented with interesting and innovative media. This shows the need to compile e-comics assisted by figma and flipbooks for the material of writing argumentative texts.